Kariera polityczna Michała Psellosa na dworze bizantyńskim w XI wieku - Domaradzki, Kamil (Acta Universitatis Lodziensis. Folia Historica, 2005)
The article presents political career of Xlth century’s intellectual, Michael Psellos. He owed his success on the Byzantine court not only to his knowledge and eloquence but also to his deviousness and ruthlessness. He held the highest court posts and offices which provided him a direct access to rulers and influence on their political decisions. Psellos had contacts with the most distinguished individuals of those times; he carried out domestic policy and, to a great extent, foreign policy of the Empire- he would put kings on thrones and faced unusually influential patriarch Michael Kerularios. Undoubtedly he was the most important political person in Emperor Isaac 1 Komnenos (1057-1059) times, who also became the ruler due to Psellos; but he also fell victim to his devious stratagem by renouncing the throne. Not all emperors, however, yielded to Psellos’s political dexterity. For instance, Roman IV Diogenes (1068-1071) considered hin as a mischievious courtier and did not trust him. Michael Psellos’s career broke about 1074/1075 during the rules of his dearest foster child, Michael Vll Doukas (1071-1078), who, following the ruthlessness of his master mentor, eliminated Psellos of political game.